THE ROLE OF KINETOTHERAPY IN THE RECOVERY OF ELBOW TRAUMA - EPICONDYLITIS IN PERFORMANCE SPORT - Florentina NECHITA (Editura Universitatii Transilvania din Brasov, 2020)
This paper presents the most effective ways of early and systematic application of kinetotherapy means and procedures to re-educate the functionality of the elbow. Movement therapy comes into action simultaneously with the other recovery means, within the general therapeutic plan, without excluding other therapies. The treatment of medial epicondylitis caused by overuse of the forearm muscles is a concern for the functional recovery of the elbow. The treatment of functional recovery of the elbow through physiotherapy is based on the functional re-education for the fastest return to the daily activities and sports of the patient. In addition to its curative role, physiotherapy, influencing a series of pathophysiological links, also has a preventive action, by improving the muscle tone of the arm, toning both the muscles of the forearm and the arm and stretching the epicondylis elbow tendons.